2016
DOI: 10.1021/acsami.6b06052
|View full text |Cite
|
Sign up to set email alerts
|

Calixarene Assisted Rapid Synthesis of Silver-Graphene Nanocomposites with Enhanced Antibacterial Activity

Abstract: Demonstrated herein is a single rapid approach employed for synthesis of Aggraphene nanocomposites, with excellent antibacterial properties and low cytotoxicity, by utilizing a Continuous Hydrothermal Flow Synthesis (CHFS) process in combination with phexasulfonic acid calix[6]arene (SCX6) as an effective particle stabilizer. The nanocomposites showed high activity against E. coli (Gram-negative) and S. aureus (Gram-positive) bacteria.The materials were characterized using a range of techniques including trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 33 publications
2
85
0
1
Order By: Relevance
“…Thus, by feeding water dispersions of 2D material into a CHFS process at different points of nucleation (i.e., before nucleation and after or during nucleation), it will be possible to fully integrate these two materials into true nanocomposites. For instance, Kellici and co‐workers also demonstrated a single rapid method of synthesising Ag/graphene nanocomposites with excellent antibacterial properties through combination with sulfonated calixarenes (Figure ) . In their work, surface‐functionalised reduced graphene oxide (rGO) through continuous hydrothermal flow method provides a support for Ag nanoparticles to prevent aggregation and also enhances bacteria adsorption due to negatively charged rGO surface.…”
Section: Synthetic Methodologies Of 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by feeding water dispersions of 2D material into a CHFS process at different points of nucleation (i.e., before nucleation and after or during nucleation), it will be possible to fully integrate these two materials into true nanocomposites. For instance, Kellici and co‐workers also demonstrated a single rapid method of synthesising Ag/graphene nanocomposites with excellent antibacterial properties through combination with sulfonated calixarenes (Figure ) . In their work, surface‐functionalised reduced graphene oxide (rGO) through continuous hydrothermal flow method provides a support for Ag nanoparticles to prevent aggregation and also enhances bacteria adsorption due to negatively charged rGO surface.…”
Section: Synthetic Methodologies Of 2d Materialsmentioning
confidence: 99%
“…In their work, surface‐functionalised reduced graphene oxide (rGO) through continuous hydrothermal flow method provides a support for Ag nanoparticles to prevent aggregation and also enhances bacteria adsorption due to negatively charged rGO surface. The Ag nanoparticles are stabilised by a class of macrocyclic compounds, calixarenes . The nanocomposites showed high activity against E. coli (Gram‐negative) and S. aureus (Gram‐positive) bacteria and in selected cases the materials were reported to outperform traditional antibiotics.…”
Section: Synthetic Methodologies Of 2d Materialsmentioning
confidence: 99%
“…Kellici et al reported a single rapid approach employed for synthesis of Ag-graphene nanocomposites, with excellent antibacterial properties and low cytotoxicity. 36 This was achieved by using a continuous hydrothermal°ow synthesis (CHFS) process in combination with p-hexasulfonic acid calix [6]arene (SCX6) as an e®ective particle stabilizer. The nanocomposites showed high activity against E. coli (Gram-negative) and S. aureus (Gram-positive) bacteria.…”
Section: Silver-based Materials To Prevent the Formation Of Bio¯lmsmentioning
confidence: 99%
“…The use of plant extracts as reducing agents will effectively reduce the environmental pollution, production cost and produces biocompatible materials. Literature has witnessed the synthesis of graphene and its composites according to the green chemistry point of view using eco‐friendly reagents such as L‐ascorbic acid, L–Lysine, glucose, tea polyphenols, mortino berry extract, Fenugreek seeds extract, E. Helioscopia L. Leaf extract, E. Bungei Bioss, W. Coagulans leaf extract, barberry fruit extract, etc …”
Section: Introductionmentioning
confidence: 99%
“…Literature has witnessed the synthesis of graphene and its composites according to the green chemistry point of view using eco-friendly reagents such as L-ascorbic acid, L-Lysine, glucose, tea polyphenols, mortino berry extract, Fenugreek seeds extract, E. Helioscopia L. Leaf extract, E. Bungei Bioss, W. Coagulans leaf extract, barberry fruit extract, etc. [17][18][19][20][21][22][23][24][25][26][27][28] Betel tree from Piperaceae family is native to Malaysia whose scientific name is Piper Betle which is popularly known as Paan in India (Vedic name-saptasira). [29] It is extensively cultivated in India, Sri Lanka and in some parts of South Asia owing to its wide use as a mouth freshener.…”
Section: Introductionmentioning
confidence: 99%